Activation of stress-related signalling pathway in human cells upon SiO2 nanoparticles exposure as an early indicator of cytotoxicity - DAVIES, ANTHONY; VOLKOV, YURI; WILLIAMS, YVONNE; PRINA MELLO, ADRIELE; KELLEHER, DERMOT P (My University, 2011)
Background: Nanomaterials such as SiO2 nanoparticles (SiO2NP) are finding increasing applications in the biomedical and biotechnological fields such as disease diagnostics, imaging, drug delivery, food, cosmetics and biosensors development. Thus, a mechanistic and systematic evaluation of the potential biological and toxic effects of SiO2NP becomes crucial in order to assess their complete safe applicability limits. Results: In this study, human monocytic leukemia cell line THP-1 and human alveolar epithelial cell line A549 were exposed to a range of amorphous SiO2NP of various sizes and concentrations (0.01, 0.1 and 0.5 mg/ml). Key biological indicators of cellular functions including cell population density, cellular morphology, membrane permeability, lysosomal mass/pH and activation of transcription factor-2 (ATF-2) were evaluated utilizing quantitative high content screening (HCS) approach and biochemical techniques. Despite the use of extremely high nanoparticle concentrations, our findings showed a low degree of cytotoxicity within the panel of SiO2NP investigated. However, at these concentrations, we observed the onset of stress-related cellular response induced by SiO2NP. Interestingly, cells exposed to alumina-coated SiO2NP showed low level, and in some cases complete absence, of stress response and this was consistent up to the highest dose of 0.5 mg/ml. Conclusions: The present study demonstrates and highlights the importance of subtle biological changes downstream of primary membrane and endocytosis-associated phenomena resulting from high dose SiO2NP exposure. Increased activation of transcription factors, such as ATF-2, was quantitatively assessed as a function of i) human cell line specific stress-response, ii) SiO2NP size and iii) concentration. Despite the low level of cytotoxicity detected for the amorphous SiO2NP investigated, these findings prompt an in-depth focus for future SiO2NP-cell/tissue investigations based on the combined analysis of more subtle signalling pathways associated with accumulation mechanisms, which is essential for establishing the bio-safety of existing and new nanomaterials.
PUBLISHED
Keywords: Biochemistry; Cytotoxicity